Analyse algébrique d'un probléme de Dirichlet non linéaire et singulier - Marti, Jean-Andre; Nuiro, Silvère P. (Topological Methods in Nonlinear Analysis, 1999)
The algebraic structure of a factor ring and the topological structure of asemi-normed algebra permit the construction of many algebras of generalizedfunctions. Some of them are well suitable to solve a non linear Dirichletproblem with irregular data.